Terapia Nutricional Enteral Em Pacientes Neurocirúrgicos - Freitas, Marcia Maria Teixeira de [UNIFESP] (2017)
Enteral Nutrition (EN) early is essential for treatment of neurosurgical disease and has association with shortest time of hospitalization. Objective: monitor the EN and assess the nutritional status of patients elective and emergency neurosurgery. Methods: Cohort study, carried in intensive care unit (ICU) of a hospital tertiary level during the 2014 to 2016 period. We included patients over the age of 18 years, with neurological diagnosis, emergency or elective surgery with EN. The data were collected in first 24 hours of introduction EN with daily monitoring. The proposed follow-up time was 14 days, with the anthropometric measurements in the first, seventh and 14th day. For estimation of nutritional needs were considered the values of 25 to 30 calories/Kg/day and 1.2 to 2.0 g/kg/day protein. Polymeric formulas and/or oligomeric, with fractionation in 3/3 hours. Calories of sedatives of lipid emulsion were considered for calculation total calories. For cases where it has not been possible to achieve goal of protein with enteral formula prescribed, additional protein module. For monitoring EN was considered the adequacy of caloric and protein supply, fasting, inadvertent output of enteral probe and gastric residue. Results: 83 patients participated in study, being 80 patients evaluated in total, of which 78,7% in emergency surgery and 21,3% elective, being mostly male with an average age of 55 years in both groups. The emergency group presented more frequently diagnosed with stroke and acute brain injury, the group of elective surgery performed brain neoplasm. Caloric and protein adequacy showed slight superiority among the patients of emergency group. It can be observed that in both groups patients showed reduction of anthropometric measurements, particularly for urgent cases. There was a higher frequency of hospital outcomes and death among patients elective group, suggesting that emergency patients remained hospitalized for more than. Conclusion: Monitoring EN was adequate caloric offer early and protein until the fourth day there. Was change of body composition sharper in the urgency group, with reduction of anthropometric measurements, because some limiters for the effectiveness of EN.